Biogas to advanced biofuels: Techno-economic analysis of one-step dimethyl ether synthesis. (20th November 2022) - Fedeli, Matteo; Negri, Francesco; Manenti, Flavio
Abstract: Bio-dimethyl ether (bio-DME) is a promising advanced biofuel for the disposal of conventional diesel fuel, which is one of the most relevant sources of particulate matter and nitrogen oxides in urban centres and is completely banned from some European cities. DME is produced in two ways: dehydration of methanol produced from syngas (indirect or two-step process) and direct synthesis from syngas (direct or one-step process). This work aims at studying, optimizing and economically and environmentally assessing a novel conceptual design to convert biogas into bio-DME. Contrarily to traditional DME processes, the synthesis from biogas strongly benefits from milder conditions due to the smaller plant size, rural context, and biological feedstock fluctuations, motivating an ex-novo techno-economic feasibility study and sensitivity analysis performed in Aspen HYSYS V11 suite. The proposed process layout allows converting 1045 kg/h of silomais-based biogas (67%v/v CH4 content) into 516 kg/h of bio-DME at ASTM D7901-14 standard specification for fuel purposes. Sensitivity analysis identifies reactor temperatures as important process variables and defines three key performance indicators as: (i) global yield of the process; (ii) DME versus methanol selectivity; (iii) and the thermal load for the downstream section. The last one is computed as the sum of reboiler and condenser duties normalized with respect to the DME massive flowrate, and the study provides 1.05 kWh/kgDME as downstream section global specific duty. The process provides an innovative way to face the EU RED II challenge due to a 49.4 wt.% bio-DME yield and also thanks to a competitive 9.5 yr of payback period. Graphical abstract: Image 1 Highlights: A conceptual design for bio-dimethyl ether (DME) synthesis from biogas is broached. Sensitivity analysis on the main operational parameters is performed. Greenhouse gas emissions are simultaneously evaluated for the purification section. CAPEX/OPEX are detailed estimated providing an appealing payback period (PBP).